Emerging Techniques in Imaging, Modelling and Visualization for Cardiovascular Diagnosis and Therapy (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The goal of this Special Issue is to disseminate emerging techniques and innovative solutions that comprehensively address unmet needs in cardiovascular disease and can be rapidly translated into the clinical arena in order to significantly improve diagnostic accuracy and precision in treatment delivery, as well as to enhance therapy guidance and procedural success. The volume includes research contributions from cross-disciplinary scientists and professionals who work in the cardiovascular field at the interface of basic and translational research, clinical practice, medical (bio)physics, engineering, mathematics, and computer science. Several compelling contributions are focused on the development of advanced techniques in cardiovascular imaging (MRI, CT, ultrasound, optics) to investigate structure–function interaction and identify pathology, image analysis (e.g. registration, segmentation, visualization), deep-learning/AI classification methods to better characterize tissue and physiological signals, novel preclinical experimental models and clinical approaches employed in electro-anatomical mapping and image-aided therapies (e.g., cardiac ablation, resynchronization), as well as innovative interventional procedures for vascular applications.